Chaihu-Longgu-Muli Decoction exerts an antiepileptic effect in rats by improving pyroptosis in hippocampal neurons. (24th April 2021) - Xia, Shuaishuai; Yang, Ping; Li, Feng; Yu, Qian; Kuang, Weiping; Zhu, Yong; Lu, Jun; Wu, Huaying; Li, Liang; Huang, Huiyong
Abstract: Ethnopharmacological relevance: Chaihu-Longgu-Muli Decoction (CLMD) is a classic prescription created by Zhong-jing Zhang, a famous ancient Chinese medical scientist, to harmonize uncontrollable body activities and calm the minds. Now Traditional Chinese Medicine (TCM) physicians often apply it to treat psychiatric diseases such as epilepsy. Aim of the study: This study investigated the mechanism of the effect of Chaihu-Longgu-Muli Decoction (CLMD) on hippocampal neurons pyroptosis in rats with Temporal Lobe Epilepsy (TLE). Materials and methods: The lithium chloride-pilocarpine-induced TLE rat model was established. The behavioral testing was performed and, the expression of IL-1β and TNF-α in serum was detected by ELISA, qRT-PCR was used to detect the mRNA expression of NLRP3, Caspase-1, IL-1β and TNF-α in hippocampus. The expression of NLRP3 and Caspase-1 in hippocampal dentate gyrus was detected by immunofluorescence assay. Results: CLMD could significantly suppress the frequency and duration time of epileptic seizures, reduce the expression of NLRP3, Caspase-1 TNF-α and IL-1β. Conclusions: CLMD exerted an obvious antiepileptic effect by improving pyroptosis in hippocampal neurons of TLE rats. Graphical abstract: Image 1